Association of Derived Neutrophil-To-Lymphocyte Ratio With Prognosis of Coronary Heart Disease After PCI - Liu, Gang-Qiong; Zhang, Wen-Jing; Shangguan, Jia-Hong; Zhu, Xiao-Dan; Wang, Wei; Guo, Qian-Qian; Zhang, Jian-Chao; Wang, Kai; Liu, Zhi-Yu; Song, Feng-Hua; Fan, Lei; Zheng, Ying-Ying; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: The role of derived neutrophil-to-lymphocyte ratio (dNLR) in predicting the prognosis of patients with coronary heart disease (CHD) who underwent percutaneous coronary intervention (PCI) has not been studied. Here, we attempted to investigate the significance of dNLR in predicting the prognosis of patients with CHD after PCI. Methods: A total of 3561 post-PCI patients with CAD were retrospectively enrolled in the CORFCHD-ZZ study from January 2013 to December 2017. 3462 were divided into three groups according to dNLR tertiles: the first tertile (dNLR<1.36; n=1139) , second tertile (1.36≥dNLR<1.96 ; n=1166) and third tertile dNLR≥1.96; n=1157). The mean follow-up time was 37.59±22.24 months. The primary endpoint was defined as mortality (including all-cause death and cardiac death), and the secondary endpoint was major adverse cardiovascular events (MACEs) and major adverse cardiovascular and cerebrovascular events (MACCEs). Results: The all-cause mortality (ACM) and cardiac mortality (CM) incidence was significantly lower in the first tertile than in the third tertile (HR =1.8, [95% CI: 1.2-2.8], P=0.006 and HR = 2.1, [95% CI: 1.23-3.8], P=0.009, respectively). Multivariate Cox regression analyses suggested that compared with the patients in the first tertile than in the third tertile, the risk of ACM were increased 1.763 times (Hazard risk (HR) =1.763, 95%CI: 1.133-2.743, P=0.012) and the risk of CM were increased 1.763 times (Hazard risk (HR) =1.961, 95%CI: 1.083-3.550, P=0.026)in the higher dNLR group during the long-term follow-up. Conclusion: The present study suggested dNLR is an independent and novel predictor of mortality in CHD patients who underwent PCI.